2004
DOI: 10.1677/joe.0.1800227
|View full text |Cite
|
Sign up to set email alerts
|

Zinc partitions IGFs from soluble IGF binding proteins (IGFBP)-5, but not soluble IGFBP-4, to myoblast IGF type 1 receptors

Abstract: Zinc (Zn 2+

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Moreover, McCusker & Novakofski (2004) have demonstrated that 125 I-Long-R3-IGF-I does not bind to IGFBP-5 and that IGFBP-5 does not affect the binding of 125 I-Long-R3-IGF-I to the type 1 IGF receptor. Taken together, we feel that our data and a large body of supporting literature have established the IGF-independent functionality of rpIGFBP-5.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, McCusker & Novakofski (2004) have demonstrated that 125 I-Long-R3-IGF-I does not bind to IGFBP-5 and that IGFBP-5 does not affect the binding of 125 I-Long-R3-IGF-I to the type 1 IGF receptor. Taken together, we feel that our data and a large body of supporting literature have established the IGF-independent functionality of rpIGFBP-5.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Zn 2+ increases IGF1 receptor sensitivity, Zn 2+ also affects IGF1 signaling in a way that Zn 2+ -deficiency may decrease IGF1 receptor binding (McCusker and Novakofski, 2004). In general, neurons control cytosolic Zn 2+ levels tightly using several ZnT transporters, ZIP transporters, and Zn 2+ buffering MTs and Zn 2+ -deficiency might influence all of the above – mentioned pathways and proteins.…”
Section: Environmental Factors In Autism – Modes Of Actionmentioning
confidence: 99%